A Need Analysis of e-Kompas Specialization Service Model for High School Student to Improve the Selection of Majors in Higher Education - Farida Aryani; Muhammad Rais; Hamdan Arfandy (Journal of Educational Science and Technology (EST), 2020)
This study aims to analyze the needs of specialization services for counselor in improving the insights of university selection using the future application of e-kompas. This research is a development research using Borg and Gall development model. This research activity focuses on need analysis activities. This research was conducted in Makassar city by involving counselor and high school student. The developed product is a future android based e-kompas application that begins with an in-depth analysis of service needs. Need analysis is done to counselor in Makassar City. The result of requirement analysis using counselor perception questionnaire about the specialization service for the selection of majors in the college for high school students shows that the counselors generally have difficulties in directing the selection of majors for high school students to continue college. Need analysis shows that counselors have a high desire to use e-kompas instrument based on android application that is practical and useful in directing high school students to choose majors in universities that match the talents, interests and potential of high school students.